Polyphenol Enriched Extract of Pomegranate Peel; A Novel Precursor for the Biosynthesis of Zinc Oxide Nanoparticles and Application in Sunscreens - Maryam Kokabi; Samad Nejad Ebrahimi (Tabriz University of Medical Sciences, 2021)
Background: Green synthesized nanoparticles (NPs) from agricultural wastes is an area of great interest due to it is eco-friendly and profitable. Zinc oxide is an inorganic UV-filter commonly used as UV-blocker in a different industry. Methods: Zinc oxide nanoparticles (ZnO NPs) were successfully biosynthesized using Zn(NO3)2 as a substrate by polyphenol enriched fraction (PEF) of pomegranate peel. The biological activity of ZnO NPs was evaluated using MBC and MIC tests for antibacterial and DPPH assay for antioxidant potential. Sunscreen potential of NPs was determined after applying them in water-in-oil emulsions. Results: UV-Vis and FT-IR spectroscopy techniques confirmed the formation of ZnO NPs. FE-SEM characterized the morphology and purity of the biosynthesized NPs with EDAX and XRD data. The average crystalline size of ZnO NPs was found to be 22 nm. FT-IR spectroscopy revealed the role of phenolic compounds in the formation and stability of ZnO NPs. The antibacterial activity of PEF and its biosynthesized ZnO was evaluated against Staphylococcus aureus and Escherichia coli. The prepared NPs showed a higher antibacterial effect than the commercial ZnO NPs. Interestingly, the antioxidant activity was also detected for obtained NPs. The PEF powder also exhibited higher antibacterial and antioxidant activity than the standards. Furthermore, the in vitro sun protection factors were estimated after applying NPs in water-in-oil emulsions. Conclusion: This study highlighted the possibility of using PEF of pomegranate peel for the biosynthesis of ZnO NPs as well as applying its NPs in sunscreens to achieve a safe alternative to harmful chemical UV-filters commonly used in cosmetics.